2022
DOI: 10.1063/5.0078865
|View full text |Cite
|
Sign up to set email alerts
|

Reversible optical control of Fano resonance and domain configuration at room temperature in BaTiO3

Abstract: Despite the ubiquitous nature, control of the Fano resonance in insulators has remained unexplored. We have achieved reversible control of Fano resonance using optical control in BaTiO3 at room temperature. Raman spectroscopic signatures and first-principle calculations suggest that the Fano line shape arises from the coupling of the discrete phonons [A(TO1)] comprising oscillations of Ba against TiO6 octahedra and broad phonons A(TO2) arising from oscillations of Ti against O6. Modifications of the A(TO2) pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…We started with structural optimization of the BTO unit cell. The lattice parameter of the relaxed tetragonal BTO unit cell was found to be a = 4 Å and c = 4.2 Å. , Using this optimized unit cell, we constructed the two configurations using a 1 a × 1 a × 12 c supercell. Configuration A (Figure a) represents a monodomain with polarization along the c -axis of the supercell, whereas in configuration B (Figure b), the dipole moment in each unit cell is modulated to mimic an interface of two ferroelectric domains with polarization pointing toward the c - and b -axis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We started with structural optimization of the BTO unit cell. The lattice parameter of the relaxed tetragonal BTO unit cell was found to be a = 4 Å and c = 4.2 Å. , Using this optimized unit cell, we constructed the two configurations using a 1 a × 1 a × 12 c supercell. Configuration A (Figure a) represents a monodomain with polarization along the c -axis of the supercell, whereas in configuration B (Figure b), the dipole moment in each unit cell is modulated to mimic an interface of two ferroelectric domains with polarization pointing toward the c - and b -axis.…”
Section: Resultsmentioning
confidence: 99%
“…20,27,43 The change observed in the line shape of A(TO 1 ) mode around 180 cm −1 also indicates modification in the local polarization. 43 A completely reverse effect was seen near the a 2 −a 1 DW, the Raman mode was found to harden (272−280 cm −1 ) (Figure 4d−f), and the asymmetric Fano line converts to the Lorentzian shape on increasing laser power (Figure 4d,e). Also, the intensity of the B 1 mode (marked by the red arrow in Figure 4a,d) near the DW regions was observed to change, which indicates a local polarization rotation resulting in the growth of a 1 subdomains at the expense of a 2 subdomains along with a shift in DW.…”
Section: X-ray Diffractionmentioning
confidence: 97%
See 1 more Smart Citation
“…The continuous band is on the high-energy side in the cases of single crystals and thin films, resulting in a negative asymmetric parameter q. 14,15,21) However, in the case of nanoparticles studied here, the q factor is always positive, which is due to the fact that the continuous state has lower energy than the discrete state. This phenomenon was also reported in other nanomaterials with similar structures.…”
mentioning
confidence: 78%
“…3) Various experimental techniques have been used to study the phase change phenomenon of BaTiO 3 , among which the noninvasive Raman spectroscopy plays an important role in determining the phase by investigating the Raman peak evolution versus temperature. [4][5][6][7][8] According to the Raman spectra of BaTiO 3 , many researchers have observed the interesting phenomenon of Fano resonance around 185 cm −1 , [9][10][11][12][13][14][15][16] which is due to the interference of a discrete energy level and a continuous band/states. 17) For example, Rousseau et al and Porto et al reported the asymmetric Raman peak around 175 cm −1 under different polarization configurations at room temperature (RT) in BaTiO 3 crystal.…”
mentioning
confidence: 99%